2018
DOI: 10.1186/s12866-018-1249-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a participant-friendly fecal collection method for microbiome analyses: a step towards large sample size investigation

Abstract: BackgroundThe effects of gut microbiota on human traits are expected to be small to moderate and adding the complexity of the human diseases, microbiome research demands big sample sizes. Fecal samples for such studies are mostly self-collected by participants at home. This imposes an extra level of complexity as sample collection and storage can be challenging. Effective, low-burden collection and storage methods allowing fecal samples to be transported properly and ensuring optimal quality and quantity of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The reason for the lack of replication between studies could be due to methodological differences. These include DNA extraction [58], 16S rRNA gene region [59], bioinformatic pipeline, data processing and analysis [60], sample size, and study design. Moreover, the age range (children vs. adults) differences between studies can underscore variation in ADHD symptoms, other non-shared environmental influences and gut microbiome composition [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the lack of replication between studies could be due to methodological differences. These include DNA extraction [58], 16S rRNA gene region [59], bioinformatic pipeline, data processing and analysis [60], sample size, and study design. Moreover, the age range (children vs. adults) differences between studies can underscore variation in ADHD symptoms, other non-shared environmental influences and gut microbiome composition [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the lack of replication between studies could be due to methodological differences. These include DNA extraction [55], 16S rRNA gene region [56], bioinformatic pipeline, data processing and analysis [57], sample size and study design. Moreover, the age range (children vs. adults) differences between studies can underscore variation in ADHD symptoms, other non-shared environmental influences and gut microbiome composition [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a -20˚C freezer is available in most homes and freezing at -20˚C may also be applied PLOS ONE [38,39] but this requires willingness to place samples in the freezer and resources for shipping the samples in a frozen state. Several studies reported positive effects of preservation media and stabilizers [11][12][13][14][15][16]. However, even if patients are asked to describe how samples were handled before submission to the laboratory, it is difficult to have complete control over what has happened and samples, for diverse reasons, may have been exposed to room temperature for hours before reaching the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…A methodological problem with analyzing stool samples, however, is that the logistics of collecting samples can vary dramatically between the subjects which may influence the composition of the microbiota and its metabolic products. The current understanding is that time and temperature appears to have a low, but not negligible impact on bacterial composition and structure in stool samples [10][11][12][13][14][15]. Immediate freezing of samples at -20˚C is considered to be the "gold standard", but might not always be practically feasible.…”
Section: Introductionmentioning
confidence: 99%